Laparoscopic surgery for removal of choledochal cysts and Roux-en-Y anastomosis - Lu, Baochun (Int J Clin Exp Med, 2015)
Choledochal cyst is prevalent in female than male. Diagnosis and management of choledochal cyst is important in clinical practice, or else, patients may develop cholangiocarcinoma. Currently, complete resection is the standard method for the treatment of choledochal cyst. However, traditional open surgery is usually needed in these procedures, which may induce postoperative injuries. In this case, we present our experiences for the management of choledochal cyst through radical removal combined with Roux-en-Y anastomosis under laparoscope. Our procedures are minimally invasive and the outcomes are satisfactory during the follow up.